Kriteria Seleksi untuk Perakitan Varietas Cabai Tahan Phytophthora capsici Leonian - Rahmi Yunianti; Sarsidi Sastrosumarjo; Sriani Sujiprihati; Memen Surahman; Sri Hendrastuti Hidayat (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
<!-- /* Font Definitions */ @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:Calibri; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:IN; mso-no-proof:yes;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> Selection criteria for developing Phytophthora blight-resistant varieties of pepper had been done in both laboratory and ﬁ eld conditions. Resistance screening were conducted on 28-days-old pepper plants grown in 72-cell ﬂ ats by inoculating 5 mL of inoculum (contain 105 zoospore mL-1) to the base of each plant. Phytophthora capsici isolate used in this experiment was TG01, which then identiﬁ ed as race-3. The evaluation of pepper genotypes characteristics were conducted in ﬁ eld. Eight characters demonstrated a wide genetic variability; those characters were resistance to Phytophthora blight, infection period, dicotomous height, canopy width, fruit weight, fruit length, fruit diameter and production. These characters along with fruit wall thickness, chlorophyll-a, chlorophyll-b, total chlorophyll had high heritability values. Using path analysis infection period, dicotomous height and fruit diameter are recommended to be simultaneously used as selection criteria for developing Phytophthora blight resistant pepper varieties. Keywords : capsicum, Phytophthora capsici, selection criteria, path analysis